The Physical and Laying Characteristics of Golden Sex-Linked Hens under the Humid Tropical Environment - Ani, A.O.; Nnamani, M.E. (Pakistan Journal of Nutrition, 2011)
A total of fifty-two Golden-sex link (brown) hens in their 65th week of lay were used in a study conducted to determine the oviposition time and interval, total egg production, clutch length and number of pause days of the birds under the humid tropical environment. The hens were also divided into four classes on the basis of their laying performances as follows: good layers, intermediate layers, poor layers and non layers and their physical conditions appraised. The birds were supplied water ad libitum and fed layers mash containing 16.5% crude protein and 9.62 MJ/kg ME for 5 weeks. Results showed that the peak of lay was between 7.30-8.30 am and declined gradually until only one egg was laid between 3.30-4.30 pm. About 66.36% and 33.64% of the eggs were laid in the morning hours and in the afternoon hours, respectively. The mean oviposition interval was 26.61 h, while the average laying intensity was 48.90%. About 98% of the clutch lengths were of 5 cycle lengths and below, with the highest frequency of occurrence being 1 cycle length. The total number of pause days over all birds was 558 days. Hens with the longest clutches and shortest number of pause days produced the greatest number of eggs. Observation made on the physical characteristics revealed that good layers had smooth and waxy comb and wattles. The vents were moist and enlarged with flexible pubic bone, soft abdomen and worn out feathers. Intermediate layers had similar features with the good layers except that eye rings, beaks and shanks were slightly bleached. Poor layers had dry combs and wattles; tight and hard abdomen and closed pubic bones. Non layers had scaly, dry and rough comb and wattles; dull eyes and rigid pubic bones which were relatively close together.